Systematic revision of the North American velvet ant genus Invreiella Suárez (Hymenoptera: Mutillidae) with description of eleven new species - Waldren, George C.; Williams, Kevin A.; Cambra, Roberto A.; Pitts, James P. (Zootaxa, 2020)
The velvet ant genus Invreiella Suárez, 1966 is redescribed and revised. Females are grouped into five species-groups, with eleven new species described based on females: I. acuminata Waldren, sp. nov., I. australis Waldren, sp. nov., I. bimaculata Waldren, sp. nov., I. breviclypeata Waldren, sp. nov., I. chihuahuensis Waldren, sp. nov., I. cuernavaca Waldren, sp. nov., I. erythrocephala Waldren, sp. nov., I. manleyi Waldren, sp. nov., I. mesomexicana Waldren, sp. nov., I. suarezi Waldren, sp. nov., and I. tequila Waldren, sp. nov. One new combination is included, I. cephalargia (Mickel, 1924), comb. nov., formerly placed in Pseudomethoca Ashmead, 1896. Additionally, I. curoei Quintero & Cambra, 2011 is synonymized with I. cardinalis (Gerstaecker, 1874), syn. nov., and I. megacantha (Cockerell & Casad, 1894), stat. resurr., is treated as a nomen dubium. The lectotype of Mutilla satrapa Gerstaecker, 1874 originally designated by C. Mickel is here validated. An illustrated key to species is included.